2014
DOI: 10.1016/j.bbmt.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Altered Mechanical and Structural Properties of Resistance Arteries in a Murine Model of Graft-versus-Host Disease

Abstract: A putative involvement of the vasculature seems to play a critical role in the pathophysiology of graft-versus-host disease (GVHD). We aimed to characterize alterations of mesenteric resistance arteries in GVHD in a fully MHC-mismatched model of BALB/c mice conditioned with total body irradiation that underwent transplantation with bone marrow cells and splenocytes from syngeneic (BALB/c) or allogeneic (C57BL/6) donors. After 4 weeks, animals were sacrificed and mesenteric resistance arteries were studied in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…However, the detailed pathomechanism underlying the initiation of aGVHD remains poorly understood. Recently, some evidences postulated that endothelial damage played an important role in the initiation of aGVHD [3, 4]. Number of circulating endothelial cells increases during the early phases of conditioning regimens, suggesting that chemotherapeutic drugs induce endothelial damage to release endogenous “danger signals” [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the detailed pathomechanism underlying the initiation of aGVHD remains poorly understood. Recently, some evidences postulated that endothelial damage played an important role in the initiation of aGVHD [3, 4]. Number of circulating endothelial cells increases during the early phases of conditioning regimens, suggesting that chemotherapeutic drugs induce endothelial damage to release endogenous “danger signals” [5].…”
Section: Introductionmentioning
confidence: 99%
“…The role of donor T cells post-allogeneic-HSCT adhering to endothelium in the vasculature as the first potential extensive area of contact with new host antigens is well established [37,38]. For chronic GVHD which exhibits a unique pathogenesis distinct from acute GVHD [39], current evidence indicates that, in addition to damage to targeted epithelia, changes to the microvascular endothelium play a role in the pathogenesis of chronic GVHD [40][41][42]. It is well known that long-term survivors after allogeneic-HSCT are at a high risk for premature arterial vascular disease [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Murine models have demonstrated the role of endothelial neovascularization induced by conditioning leading to GvHD (9193) and infiltrating donor T cells. Recently, Schmid et al showed for the first time in a murine system that not only endothelial venules but also arterial vessels suffer direct endothelial damage during GvHD (94). Detailed studies in patients have shown an association of loss of dermal vessels, with CD8+ T cell infiltrates, demonstrating allogeneic reactions against endothelial cells (95, 96).…”
Section: Further Hsct-related Complicationsmentioning
confidence: 99%